2015
DOI: 10.4028/www.scientific.net/kem.662.257
|View full text |Cite
|
Sign up to set email alerts
|

Short Overview of the Effects of Nanoparticles on Mechanical Properties of Concrete

Abstract: Short survey of the literature revealed that the addition of nanoparticles, e.g., nano- SiO2, Al2O2, CuO, TiO2, ZnO2, Fe2O3, Cr2O3 in concrete result in improvement of its physical and mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Based on the literature review, it can be concluded that the content of microsilica in cementitious materials varies from 1.0 to 30.0 wt.%, nevertheless the recommended amount appears to be in the range from 5.0 to 15.0 wt.% [17]. At the same time, a dosage of nanoparticles varies from 0.5 to 12.0 wt.%; however, the optimum range appears to be between 1.0 and 4.0 wt.% [18]. In both situations amount of additive depends on the type of base material (cement paste, mortar, concrete) and the aim of the modification.…”
Section: Introductionmentioning
confidence: 97%
“…Based on the literature review, it can be concluded that the content of microsilica in cementitious materials varies from 1.0 to 30.0 wt.%, nevertheless the recommended amount appears to be in the range from 5.0 to 15.0 wt.% [17]. At the same time, a dosage of nanoparticles varies from 0.5 to 12.0 wt.%; however, the optimum range appears to be between 1.0 and 4.0 wt.% [18]. In both situations amount of additive depends on the type of base material (cement paste, mortar, concrete) and the aim of the modification.…”
Section: Introductionmentioning
confidence: 97%
“…Recent research on the influence of nanoparticle addition in the geopolymer composition has shown that compressive strength, bending strength and abrasion resistance as well as the workability can be improved by using silica and alumina nanoparticles [9]. The amount of nanoparticles related to the amount of cement is effective for properties of geopolymer concrete between 0.2-1.2 wt.…”
Section: Introductionmentioning
confidence: 99%
“…There is hope that this approach can also successfully improve the adhesion of the cement mortar used to make the overlay to the concrete substrate, as well as improve its functional properties. Based on an analysis of the subject of the literature concerning, e.g., the application of nanoparticles as an addition to the cement mortar used to make the overlay [45,46,47,48,49,50,51,52,53], one can see opportunities to improve its adhesion with the substrate and improve its functional properties.…”
Section: Introductionmentioning
confidence: 99%